Sohbet: Revitalization of the Hizmet/Gülen Movement in Finland through Spiritual Gatherings - Neval, Emine (Approaching Religion, 2024)
Sohbet (conversation) is a weekly, informal, religious-learning gathering that has been conducted by members of the Islamic Hizmet/Gülen Movement since its inception. The movement was established in Turkey in 1966 by Fethullah Gülen and his followers. It has evolved into a transnational social movement through educational, dialogical, and humanitarian aid/entrepreneurial activities. The movement was held responsible by the Turkish government for the so-called coup attempt in 2016. Tens of thousands of members fled, and the movement’s centre of gravity shifted from Turkey to the diaspora. This ethnographic research project addresses the transformations within the movement during the diaspora phase. Focusing on a female sohbet group in Helsinki, I investigate the participants’ understandings of sohbet and how the sohbet has evolved since 2016. Thematic analysis reveals three predominant themes for understanding: socialization, belonging to a community, and a quest for piety. This article illustrates that sohbet is a space for religious learning, social interactions, and affirming a shared identity that shapes the hizmet habitus. Furthermore, sohbet revitalized the hizmet habitus following the forced migration. This study contributes to the existing literature on the sohbet by investigating it post-migration. Simultaneously, it contributes to studies on religious movements and how migration affects them.